2016
DOI: 10.3389/fped.2016.00011
|View full text |Cite
|
Sign up to set email alerts
|

Resting State EEG Hemispheric Power Asymmetry in Children with Dyslexia

Abstract: Dyslexia is a neurodevelopmental disorder estimated to affect between 4 and 7% of the population. It is often referred to as a learning disability and is characterized by deficits in the linguistic system. To better understand the neural underpinnings of dyslexia, we examined the electroencephalography (EEG) power spectra between pre-adolescents with dyslexia and neurotypical control children during eyes closed state. We reported the differences in spontaneous oscillatory activity of each major EEG band (delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 53 publications
(52 reference statements)
3
29
1
Order By: Relevance
“…EEG spectral differences have been used to differentiate matched controls from those with pathological conditions like dyslexia (Galin et al, 1992;Papagiannopoulou and Lagopoulos, 2016), insomnia (Buysse et al, 2008), fibromyalgia (Gonzalez-Roldan et al, 2016), epilepsy (Adebimpe et al, 2015), adolescents with sports related concussions (Balkan et al, 2015), and Parkinson’s disease (Caviness et al, 2016). In the current study, μ-β amplitudes did not correlate with a behavioral measure of stuttering severity making it unclear how well μ-β amplitude defines the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…EEG spectral differences have been used to differentiate matched controls from those with pathological conditions like dyslexia (Galin et al, 1992;Papagiannopoulou and Lagopoulos, 2016), insomnia (Buysse et al, 2008), fibromyalgia (Gonzalez-Roldan et al, 2016), epilepsy (Adebimpe et al, 2015), adolescents with sports related concussions (Balkan et al, 2015), and Parkinson’s disease (Caviness et al, 2016). In the current study, μ-β amplitudes did not correlate with a behavioral measure of stuttering severity making it unclear how well μ-β amplitude defines the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…However, this resource may be useful in future therapeutic or brain stimulation intervention trials [31].…”
Section: P300 Auditory Cognitive Evoked Potential As a Tool For Monitmentioning
confidence: 99%
“…Previous studies investigated the auditory P300 component in individuals with dyslexia and reported different results: increased latency and decreased amplitude when compared to controls [31], no significant changes observed for the P300 amplitude and increased latency in the dyslexic group [32], and no significant between-group differences in the P300 amplitude and latency [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent fMRI studies in neurotypical adults implicate corticostriatal and hippocampal systems in language learning [27]. In the literature, it has been further shown that higher levels of slow brain waves in the Broca area (F7 and FC5) in the left hemisphere have a high correlation with linguistic learning disabilities [5], [6], [10], [21], [25], [26]. These studies have been completed 978-1-5386-1501-0/18/$31.00 c 2018 IEEE using laboratory EEG equipment with 32 or 64 electrodes.…”
Section: Introductionmentioning
confidence: 99%